Post‐transplant monitoring of NK cell counts as a simple approach to predict the occurrence of opportunistic infection in liver transplant recipients. Issue 4 (2nd August 2016) - Fernández‐Ruiz, M.; Silva, J.T.; López‐Medrano, F.; Allende, L.M.; San Juan, R.; Cambra, F.; Justo, I.; Paz‐Artal, E.; Jiménez, C.; Aguado, J.M.
Abstract: Background: Monitoring of peripheral blood lymphocyte subpopulation (PBLS) counts might be useful for estimating the risk of infection after liver transplantation (LT). Methods: We prospectively measured total lymphocyte and PBLS counts at baseline and post‐transplant months 1 and 6 in 92 LT recipients. PBLS were enumerated by single‐platform 6‐color flow cytometry technology. Areas under receiver operating characteristic (ROC) curves were used to evaluate the accuracy of different PBLS for predicting cytomegalovirus (CMV) disease and overall opportunistic infection (OI). Adjusted hazard ratios (aHRs) for both outcomes were estimated by Cox regression. Results: After a median follow‐up of 730.0 days, 29 patients (31.5%) developed 38 episodes of OI (including 22 episodes of CMV disease). The counts of CD3 +, CD4 +, and CD8 + T cells, and CD56 + CD16 + natural killer (NK) cells at month 1 were significantly lower in patients subsequently developing OI. The NK cell count was the best predictive parameter (area under ROC curve for predicting CMV disease: 0.78; P ‐value = 0.001). Patients with an NK cell count <0.050 × 10 3 cells/μL had higher cumulative incidences of CMV disease ( P ‐value = 0.001) and overall OI ( P ‐value <0.001). In the multivariate models, an NK cell count <0.050 × 10 3 cells/μL at month 1 post transplantation remained as an independent risk factor for CMV disease (aHR: 5.54; P ‐value = 0.003) and overall OI (aHR: 7.56; P ‐value <0.001). Conclusion: Post‐transplant kinetics of NK cell counts may be used as a simple and affordable proxy to the cell‐mediated immunity status in LT recipients and to their associated risk of OI.